Baitul Mal Wat Tamwil Architectural Map: Institutional and Regulatory Analysis - Pupun Saepul Rohman; Nisful Laila; Atina Shofawati (Universitas Muhammadiyah Sidoarjo, 2022)
Bait al-maal wa al-tamwiil is a sharia microfinance concept that only exists in Indonesia. There is a uniqueness in the concept, namely the merging of social activities with commercial activities in one institution. This institution was born along with the birth of Islamic banking in Indonesia. This study collects a number of literatures to describe the architectural map of BMT in Indonesia. Currently BMTs mostly operate under Law no. 25 of 1992 concerning Cooperatives and a few others operate under the Financial Services Authority (OJK) through Law no. 1 of 2013 concerning Microfinance Institutions (MFIs). The DSN MUI fatwa which is the basis for the existence of BMT is the DSN-MUI Fatwa No. 141/DSN-MUI/VIII/2021 concerning Guidelines for the Establishment and Operation of Sharia Cooperatives.